Mapping Creativity through Socially Engaged Visual Arts: Art Projects in two Amadora Neighborhoods - Pinto, António Gorgel (Street Art & Urban Creativity, 2015)
This article addresses the notion of the socially engaged visual arts. The first part explores some fundamental historical periods to help understand this practice, from the Greek concept of teknè until the present time. Then, the idea of a machine for the emancipation of creativity is explained, as well as its operation in two neighborhoods of the Portuguese city of Amadora. Finally, as a result of this immaterial machine, the focus turns to a detailed description of an archive of audiovisual elements that represents each activity undertaken within the project.